Origin and timing of volatile delivery (N, H) to the angrite parent body: Constraints from in situ analyses of melt inclusions. (15th November 2021) - Deligny, C.; Füri, E.; Deloule, E.
Abstract: Angrites are derived from the earliest generation of differentiated planetesimals that accreted sunward of Jupiter's orbit, and are, thus, key to constraining the timing and source(s) of volatile delivery to planetary bodies in the inner solar system. Here we investigate the nitrogen and hydrogen isotopic signatures of angrite melts by in situ secondary ion mass spectrometry (SIMS) analyses of mineral-hosted melt inclusions and interstitial glass in two of the oldest volcanic angrites: D'Orbigny and Sahara 99555. The most primitive melt trapped in Mg-rich olivines in D'Orbigny is characterized by δ 15 N values ranging from 0 ± 25 to +56 ± 29‰ and δD values between −348 ± 53 and −118 ± 31‰. This shows that the angrite mantle source sampled by D'Orbigny has a N-H isotopic composition that is similar to that of CM carbonaceous chondrites, whose parent bodies are thought to have accreted in the outer solar system. The low nitrogen and water contents measured in Sahara 99555 possibly indicate that its parental melt underwent a higher degree of degassing compared to D'Orbigny or, alternatively, that the two angrites do not sample the same volatile reservoir within the angrite parent body. Given the very old crystallisation age of D'Orbigny, our findings imply that nitrogen- and water-rich objects, presumably formed beyond the orbit of Jupiter, must have been present in the terrestrial planet-forming region within the first ~4 Ma after the formation of Ca-Al-rich inclusions (CAIs, the oldest materials in the solar system).